APPRAISAL OF ALTERNATIVE SOURCES OF FINANCING PUBLIC PRIMARY EDUCATION FOR QUALITY ASSURANCE IN MAKURDI EDUCATION ZONE OF BENUE STATE, NIGERIA (Journal of Association of Educational Management and Policy Practitioners, 2024)
This study investigated appraisal of alternative sources of financing public primary education for quality assurance in Makurdi Education Zone of Benue State, Nigeria. Two research questions guided the study and two hypotheses were formulated and tested at 0.05 level of significance. Descriptive survey research design was adopted for the study. The population of the study was 2,174 teachers in 378 public primary schools in Makurdi Education Zone of Benue State. A sample of 217 teachers was selected from 19 public primary schools in Makurdi Education Zone of Benue State. The simple random sampling technique was used to select the respondents. A 10-item questionnaire on a structured fourpoint rating scale titled ―Appraisal of Alternative Sources of Financing Public Primary Education Questionnaire (AASFPPEQ)‖ was used for data collection. Two experts in the Faculty of Education, Benue State University, validated the instrument. The reliability of the instrument was ascertained through trial testing using Cronbach Alpha statistics, which yielded reliability co- efficient of 0.87. This indicated that the instrument was reliable for usage. Data obtained from the study were analyzed using Mean scores and Standard Deviation to answer the research questions and Chisquare (χ2) test of goodness of-fit to test the null hypotheses at 0.05 level of significance. The findings indicated that contributions from old students association and sale of proceeds from school farms has significant influence on primary education for quality assurance in Makurdi Education Zone of Benue State, Nigeria. It was recommended among others that school administrators should intensify efforts at creating a good relationship with old students association so that they could be encouraged to contributing their finances in the administration of schools geared towards quality assurance.